Fostering Muslim-Christian Tolerance in Schools through Multicultural Counseling Programs: A Preventive Psychoeducation Model - Baruno, Yosep Heristyo Endro; Sayono, Sayono; Maulana, Muhammad Rizza (Yayasan Minang Darussalam, 2025)
Background. Religious diversity in schools often presents challenges related to interfaith tension, prejudice, and social exclusion, particularly between Muslim and Christian students. Traditional educational approaches tend to lack the psychological depth needed to foster sustainable tolerance and inclusive interactions among students from different faith backgrounds. Purpose. This study aimed to develop and examine a preventive psychoeducation model within multicultural counseling programs designed to foster Muslim-Christian tolerance in secondary schools. The research explored the role of initial attitudes, multicultural knowledge, and bias sensitivity in shaping students’ preventive competence and promoting harmonious coexistence. Method. A qualitative case study approach was used, involving several secondary schools in religiously diverse regions. Data were collected through in-depth interviews, participatory observation, and document analysis involving school counselors, religious teachers, and students. Structural equation modeling using SmartPLS and ANOVA correlation analysis were employed to explore the relationships among the variables. Results. The findings revealed that positive initial attitudes significantly influenced multicultural knowledge acquisition, which in turn enhanced preventive competence. Multicultural knowledge had the strongest impact on students’ ability to proactively manage religious diversity. However, bias sensitivity showed a weaker or even negative correlation with competence, indicating the need for emotional regulation in counseling interventions. The final outcome—harmonious interfaith interaction—depended not only on individual competencies but also on broader school dynamics. Conclusion. The preventive psychoeducation model rooted in multicultural counseling offers a promising strategy for promoting interfaith tolerance in schools. It highlights the importance of addressing both cognitive and emotional domains to prepare students for peaceful coexistence. Implementation of such models requires institutional support, professional counselor training, and integration with school culture and policies.